THE EFFECT OF INTELLECTUAL CAPITAL, INVESTMENT OPPORTUNITY SET (IOS), BUSINESS RISK AND CORPORATE SOCIAL RESPONSIBILITY (CSR) ON COMPANY VALUE IN COMPANIES PROPERTY AND REAL ESTATE REGISTERED ON THE INDONESIAN STOCK EXCHANGE - Dwi Selvi Wulandari; Husaini; Jummaini; Wardhiah (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to examine the effect of intellectual capital, investment opportunity set (ios), business risk and corporate social responsibility (csr) on firm value in property and real estate companies listed on the Indonesia stock exchange. Research data can be accessed on the official website www.idx.co.id. The sampling method used purposive sampling and obtained a sample of 18 companies for the 2019-2023 period. The results found that VAIC and CSR have a positive and insignificant effect, while MBVA has a positive and significant effect and EBP has a negative and significant effect on firm value.